A Multimodal Analysis Of Public Health Posters On Ten Killer Diseases In Katsina State, Nigeria - Abdulhakim, Saidu (2025)
This research presents a multimodal analysis of public health posters (php) on ten killer diseases in katsina state, nigeria. Public health posters are vital tools for disease prevention campaigns, often used to disseminate information about disease causes, symptoms, and prevention strategies. Despite their widespread use, limited research has evaluated their effectiveness, particularly in northern nigeria. This study aims to fill that gap by analyzing how these posters communicate through language and images. The research employs a multimodal approach, using cheong's (2004) generic structure potential (gsp), van leeuwen‘s (2008) social actor network, and martinec & salway‘s (2005) system of logico-semantic relations to evaluate the generic structure, language, and image features, as well as the interaction between language and image. A sample of 100 posters from various hospitals in katsina state was analyzed. Findings indicate that php has distinct structural patterns and relies heavily on the interplay between language and visuals to convey messages. While images support the information conveyed by the text, the posters often depend on linguistic explanations to achieve clarity.